US immigration Westernizes the human gut microbiome - Vangay, P; Johnson, A; Ward, T; Al-Ghalith, G; Shields-Cutler, R; Hillmann, B; Lucas, S; Beura, L; Thompson, E; Till, L; Batres, R; Paw, B; et al. (Cell Press, 2018)
Many US immigrant populations develop metabolic diseases post immigration, but the causes are not well understood. Although the microbiome plays a role in metabolic disease, there have been no studies measuring the effects of US immigration on the gut microbiome. We collected stool, dietary recalls, and anthropometrics from 514 Hmong and Karen individuals living in Thailand and the United States, including first- and second-generation immigrants and 19 Karen individuals sampled before and after immigration, as well as from 36 US-born European American individuals. Using 16S and deep shotgun metagenomic DNA sequencing, we found that migration from a non-Western country to the United States is associated with immediate loss of gut microbiome diversity and function in which US-associated strains and functions displace native strains and functions. These effects increase with duration of US residence and are compounded by obesity and across generations.